Research on vulnerability and security technology of industrial Ethernet protocol - Tao FENG; Ye LU; Jun-li FANG (Tongxin xuebao)
To solve the information security of industrial control system,the safety of industrial Ethernet protocol was studied deeply,the research status of protocol security protection was reported and the vulnerability of the five-major protocol was analyzed.Firstly,the architecture of industrial control system and industrial Ethernet protocol was discussed.Secondly,from the three aspects of external active defense technology,internal passive defense technology and protocol security improvement,a perfect industrial Ethernet protocol security protection model was put forward,and the main protection technology was discussed.Finally,the future development direction and research ideas of information security improvement of industrial Ethernet protocol were pointed out.